The Future of Writing - Dunne, Professor Anthony; Banks, Richard; Taylor, Alex; Kular, Onkar; Benqué, David; Macdonald, Dash; Kargotis, Demitrios; Barhad, Kobe; Myers, Nicolas; Pohflepp, Sascha; Woebken, Chris; Kellenberger–White; et al. (2011)
The Future of Writing was a design project commisioned by Microsoft Research Cambridge and the Microsoft Office team from the Royal College of Art in London. In this project five teams of design alumni from the college took a speculative approach to looking at the way in which authorship may change in the future. The result was five very diverse directions, described using video, text, images and interactive prototypes. This document describes the ideas, research and output of this project in detail.